PENGEMBANGAN MEDIA KOSABANG UNTUK MENINGKATKAN MINAT BELAJAR SISWA PADA MATA PELAJARAN IPS SISWA KELAS IV SD - Nila Septri Setiawati; Maharani Oktavia; Kiki Aryaningrum (JURNAL HANDAYANI PGSD FIP UNIMED, 2022)
Abstract: Interest in learning is an impulse that arises from within oneself to learn something from those who do not know. Therefore, the difficulty that arises is the low interest of students in learning, especially in social studies subjects. Based on this, the problem in this research is the learning media in the form of comics to increase students' interest in learning in social science subjects for class IV in elementary school. The purpose of this research is to develop comic media to increase students' interest in learning in social science subjects for grade IV in elementary school. This study uses the Research and Development method using the ADDIE model. The results of the research from the validation of experts get a percentage value of 89% with the criteria of "very feasible", from the one-to-one trial it gets a percentage value of 96% in the "very feasible" category and the results from the small group trial get a percentage value of 92.6% with the category of "very high improvement" it can be said that comics media are feasible to use and can increase students' interest in learning in social science subjects for grade IV elementary school.Keywords: Media, Interest in Learning, Social Studies, Comics, Research and Development, and ADDIEAbstrak: Minat belajar merupakan dorongan yang muncul dari dalam diri sendiri untuk mempelajari sesuatu dari yang tidak tahu menjadi tahu. Oleh karena itu, kesulitan yang muncul adalah rendahnya minat belajar siswa dalam belajar terkhusus pada mata pelajaran IPS. Berdasarkan hal tersebut maka masalah dalam penelitian ini adalah Bagaiman kelayakan media pembelajaran berupa komik untuk meningkatkan minat belajar siswa pada mata pelajaran IPS kelas IV di SD. Tujuan penlitian ini mengembangkan media komik untuk meningkatkan minat belajar siswa pada mata pelajaran IPS kelas IV di SD. Penelitian ini menggunakan metode Research and Development dengan menggunakan model ADDIE. Hasil penelitian dari keseluruhan validasi para ahli mendapatkan presentase nilai 89% dengan kriteria “sangat layak”, dari uji coba one to one mendapatkan presentase nilai 96% dengan kategori “sangat layak” dan hasil dari uji coba small group mendapatkan presentase nilai 92,6% dengan kategori “peningkatan sangat tinggi” maka dapat disimpulkan media komik layak untuk digunakan dan dapat meningkatkan minat belajar siswa pada mata pelajaran IPS kelas IV SD.Kata Kunci: Media, Minat Belajar, IPS, Komik, Penelitian dan Pengambangan, dan ADDIE